2014
DOI: 10.17221/930/2013-pse
|View full text |Cite
|
Sign up to set email alerts
|

Influence of long-term fertilizer application on changes of the content of Mehlich-3 estimated soil macronutrients

Abstract: The aim of this work is to evaluate the changes of Mehlich 3 -P, K, Ca and Mg contents in soil during a long-term field experiments with sewage sludge, farmyard manure (FYM) and mineral NPK (NPK) application, compared to the control non-fertilized treatment. The experiment was established at the Humpolec and Suchdol sites (Czech Republic). Potatoes, wheat and barley were grown in crop rotation. Fertilizing system was based on the same nitrogen dose of 330 kg N/ha per one crop rotation. Archive soil samples fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 28 publications
2
8
0
Order By: Relevance
“…9). In agreement with these findings, Kulhánek et al (2014) found increased Mg availability from FYM amendment accompanied by limited effects on available Ca which appeared to decline towards the end of a 15-year experiment. The highly variable effects of BIO and BCW on plant-available Ca and Mg lend support to some previous studies (Schulz and Glaser 2012;Tsetsegmaa et al 2018) but also contradict others (Ciecko et al 2015;Agegnehu et al 2016).…”
Section: Soil Fertilitysupporting
confidence: 82%
See 1 more Smart Citation
“…9). In agreement with these findings, Kulhánek et al (2014) found increased Mg availability from FYM amendment accompanied by limited effects on available Ca which appeared to decline towards the end of a 15-year experiment. The highly variable effects of BIO and BCW on plant-available Ca and Mg lend support to some previous studies (Schulz and Glaser 2012;Tsetsegmaa et al 2018) but also contradict others (Ciecko et al 2015;Agegnehu et al 2016).…”
Section: Soil Fertilitysupporting
confidence: 82%
“…The total C, N and S contents of soil and organic amendments were measured by a CNS elemental analyser (Vario Micro Cube, Elementar Analysensysteme GmbH, Germany). The plant-available K, Mg, Ca and P contents of soil were determined by the Mehlich-3 method (Mehlich 1984;Kulhánek et al 2014) due to its relative suitability to acidic soils than other methods (e.g. the Olsen test).…”
Section: Analyses Of Soil and Organic Amendmentsmentioning
confidence: 99%
“…There are several positive aspects of this fertilizer combination (FYM N3) on soil properties, such as: (1) accumulation of total and plant-available nutrients (Kulhánek et al ., 2014; Mazur and Mazur, 2015); (2) physical improvements as a result of better aggregate stability, water infiltration rate, water holding capacity, structure quality and porosity (Barzegar et al ., 2002; Pagliai et al ., 2004); (3) advantages in soil microbial biomass and activity (Clark and Hirsch, 2008; Tlustos et al ., 2017); and (4) enhanced soil fertility (Edmeades, 2003; Maltas et al ., 2013; Johnston and Poulton, 2018). All these positive aspects provide more favourable growing conditions for wheat plants and may improve the buffer function (resilience) of the soil, which reduces the negative impact of biotic and abiotic stressors on plants and finally results in higher yields and reduced yield risks in wheat, as observed in the Broadbalk Experiment at Rothamsted.…”
Section: Discussionmentioning
confidence: 99%
“…Cellulose production waste does not contain nitrogen, which results (among other things) from technological processes (Buzzini and Pires 2002). The high calcium content in the municipal sewage sludge and cellulose production waste, resulting from the technology of stabilization of these wastes, is beneficial in the aspect of deacidification of acid soils and improvement of their physicochemical properties (Pérez-López et al 2008;Kulhánek et al 2014). In the applied wastes, an average content of phosphorus and magnesium comparable to other sewage sludges was recorded (Kominko et al 2017).…”
Section: Chemical Composition Of Cellulose Production Waste and Municmentioning
confidence: 99%